1999
DOI: 10.1097/00004836-199906000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Arterial Chemoembolization for Hepatocellular Carcinoma in Patients With Child's Grade A or B Cirrhosis

Abstract: We evaluated factors affecting long-term survival after transcatheter arterial chemoembolization (TACE) for hepatocellular carcinoma (HCC) complicating cirrhosis. One hundred eighty-two patients with Child's class A or B cirrhosis and an HCC, not amenable to surgery or percutaneous ethanol injection, underwent 346 TACEs (mean 1.9) with epirubicin, iodized oil, and gelatin sponge. Many prognostic factors were subjected to univariate analysis and thereafter, when significant, to the Cox's hazard proportional mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
20
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 29 publications
7
20
0
1
Order By: Relevance
“…Ascites has been reported to be a poor prognosis factor by Savastano et al [23]. In our study, the hazard ratio was 2.727.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Ascites has been reported to be a poor prognosis factor by Savastano et al [23]. In our study, the hazard ratio was 2.727.…”
Section: Discussionsupporting
confidence: 59%
“…The number of tumor lesions and the diameter of the tumor have also been reported as poor prognosis factors in other studies [21][22][23][24]. It is known that HCC elevates the degree of malignancy from a well-differentiated to a moderately or poorly differentiated tumor concomitantly with an increase in the diameter of the tumor.…”
Section: Discussionmentioning
confidence: 94%
“…Previous study showed that the reduced serum level of AFP after intervention, the number of TACE procedures, small tumor size anda homogenous tumor uptake are related to the prognosis of patients treated with TACE (Okuda et al, 1984;Mondazzi et al, 1994;Farinati et al, 1996;Savastano et al, 1999;Lee et al, 2002;Lopez et al, 2002), which showed the difference on the prognosis of HCC could be due to ethnicity, characteristics of patients or chance.…”
Section: Discussionmentioning
confidence: 99%
“…Transarterial chemoembolization in combination with embolic agents such as gelatin particles may cause considerable side effects (23). Because of their less permanent occlusion of blood flow, DSMs are expected to reduce toxicity levels and adverse events (24,25).…”
Section: Discussionmentioning
confidence: 99%